Free printing is the brake of the ambitious - Sánchez Carrión, José Faustino (1988)
We totally exclude religions, following the example of the Cortes of Cádiz in what we believe gave one of the proofs of their wisdom. Tell yourself that we are intolerant: this matters little. We do not want the horrible scenes of France to be renewed in our Homeland. There is not a single thinker who does not inculcate the necessity of this principle, and on what should be recognized by constitutional law. Free printing is the brake of the ambitious.